Perubahan frekuensi konsumsi makanan dan hubungannya dengan kerawanan pangan selama pandemi COVID-19 di Kota Yogyakarta: Studi Cross-Sectional - Nai, Hildagardis Meliyani Erista (Poltekkes Kemenkes Aceh, 2025)
Background: The number of poor people in Yogyakarta City increased by 7,37% compared to the previous year in 2020 and 2021. The scale of household hunger in Daerah Istimewa Yogyakarta Province was 6% before the pandemic and increased during the pandemic to 11%. The research question of this study is whether there is a change in the frequency of food consumption during the COVID-19 pandemic in Yogyakarta City and whether there is a relationship between food insecurity and the frequency of food consumption in Yogyakarta City.Objectives: This study aims to compare the frequency of food consumption among Yogyakarta City people aged 20–54 before and during the COVID-19 pandemic.Methods: This study used cross-sectional design.The research was conducted in Yogyakarta City from February 2021 to February. There were 357 people involved in this study. The sample was selected using multistage random sampling.Data were collected using interview techniques and filling out respondent identity questionnaires, Food Frequency Questionnaire (FFQ), and Household Food Insecurity Access Scale (HFIAS). Data were analyzed descriptively and analytically.The difference test used the Wilcoxon Signed Ranks Test. Relationship between food security status and frequency of food consumption during the COVID-19 Pandemic used the Spearman's rank Correlation Test.Results: The results showed that there was a difference in the frequency of consumption of vegetables and fruit between before and during the COVID-19 pandemic (p= 0,035; p=0,010). There was a significant relationship between food insecurity during the COVID-19 pandemic and the frequency of consumption of staple foods (p=0,04;r=-0,10), milk/dairy products (p=0,02;r=-0,12), meat (p=0,00,r=-0,28), fish/seafood (p=0,00;r=0,33), and fruit (p=0,00;r=-0,19).Conclusion: Fruit and vegetable consumption has increased during the COVID-19 pandemic compared to pre-pandemic levels. There was a significant relationship between food insecurity during the COVID-19 pandemic and the frequency of consumption of staple foods, milk, meat, fish/seafood, and fruit. Public health strategies should ensure access to affordable sources of animal for food-insecure populations during health crises.